2017
DOI: 10.1590/0001-3765201720170040
|View full text |Cite
|
Sign up to set email alerts
|

Oral insulin improves metabolic parameters in high fat diet fed rats

Abstract: Introduction/Aim: The gut has shown to have a pivotal role on the pathophysiology of metabolic disease. Food stimulation of distal intestinal segments promotes enterohormones secretion influencing insulin metabolism. In diabetic rats, oral insulin has potential to change intestinal epithelium behavior. This macromolecule promotes positive effects on laboratorial metabolic parameters and decreases diabetic intestinal hypertrophy. This study aims to test if oral insulin can influence metabolic parameters and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…Conversely, HG-NPI showed significant reduction of retroperitoneal fat pads compared to HG-NP. A similar trend of reduction was observed by Lipinski [15] in nondiabetic rats receiving oral insulin treatment, and the authors argued whether topical insulin can directly impact gut epithelial lipid metabolism. Figure 5 shows the baseline blood glucose data of the animals.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Conversely, HG-NPI showed significant reduction of retroperitoneal fat pads compared to HG-NP. A similar trend of reduction was observed by Lipinski [15] in nondiabetic rats receiving oral insulin treatment, and the authors argued whether topical insulin can directly impact gut epithelial lipid metabolism. Figure 5 shows the baseline blood glucose data of the animals.…”
Section: Resultssupporting
confidence: 72%
“…The research showed a decrease in triglycerides in animals treated with gold nanoparticles coated with polysaccharide extracted from an apple. In a previous study, Lipinski [15] also observed a reduction in triglyceride levels with the use of oral regular insulin.…”
Section: Resultsmentioning
confidence: 73%
“…Blood was collected from animals and centrifuged at 3,000 rpm for 10 minutes, before measuring the following: a) glucose, b) triglycerides, c) total cholesterol, d) total proteins (all by enzymatic colorimetric methods) [25], and e) Plasma insulin, determined by radioimmunoassay [26].…”
Section: Serum Analysismentioning
confidence: 99%
“…Insulin is a peptide that has low bioavailability when administered orally due to its degradation in stomach pH. However, studies show that this hormone improves serum parameters and promotes morphologically changes in the intestinal epithelium [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, insulin is able to act by reducing the weight of adipose tissue [2]. The cause of the inflammation in adipocytes caused by diabetes is not yet fully defined.…”
Section: Introductionmentioning
confidence: 99%